Analisis Rekomendasi Penggunaan Provider Telekomunikasi Seluler Berdasarkan Pengukuran Bandwdith pada Masa Pandemi - Hadryan Eddy; Kusrini Kusrini; Asro Nasiri (STMIK AKBA, 2021)
This study aims to provide recommendations for the use of cellular telecommunicationsproviders for use in online learning during a pandemic. This study used an experimental studyin which the researcher collected data manually by comparing the download and uploadbandwidth usage of each available cellular telecommunications provider in the Mamujudistrict. This research was conducted during the COVID-19 pandemic to impact the teaching and learning process, which must do online or remotely, which certainly requires good internetconnectivity. This research uses quantitative methods and comparative analysis by collectingdata download bandwidth and upload bandwidth using NetLimiter from three cellulartelecommunications providers, namely Telkomsel, XL, and Indosat in Mamuju district. Thenthe data is processed by calculating the bandwidth. The results of data analysis obtained areTelkomsel with a download bandwidth of 0.0136 MBps, upload 0.0147 MBps, XL downloadbandwidth 0.0116 MBps, upload 0.0129 MBps, Indosat download bandwidth 0.0066 MBps,upload 0.0162 MBps. The results of this study show that among the three providers, Telkomselis superior in the use of download bandwidth with a size of 0.0136 MBps. In contrast, forupload bandwidth usage, it is recommended to use Indosat with a size of 0.0162 MBps. Still,an overall analysis of the provider, Telkomsel is a recommended provider for using videoconferencing applications due to gaps Between the download bandwidth usage with a size of0.0136 MBps and upload with a size of 0.0147 MBps is not too significant and more stablethan other providers. Suggestions for further research are re-measurement by looking at thedistribution factor or the number of BTS in the area